Perceived protective behavioral changes in Chinese residents post-dynamic zero-COVID policy lifting: a cross-sectional study - Song, Yuan-Yuan; Xu, Ling; Liu, Dan; Feng, Mei; Yang, Cui; Jiang, Yan; Wu, Ying (Frontiers in Public Health, 2024)
ObjectiveTo investigate how Chinese residents perceived changes in their protective behaviors in the early stage after the lifting of the dynamic zero-COVID policy, and to explore the associations between the overall perceived change and factors such as demographic and health-related information, COVID-19 related perceptions, negative emotions, and coping styles.MethodsThis cross-sectional study involved 798 Chinese residents who completed an online questionnaire between 16 and 25 December 2022. The questionnaire covered demographic and health-related information, COVID-19 related perceptions, negative emotions, coping styles, and perceived changes in protective behaviors. Multiple linear stepwise regression analysis was used to determine the factors associated with the overall perceived change in protective behaviors.ResultsThe mean score for perceived protective behavioral change among participants was 61.38 (SD = 10.20), which was significantly higher than the hypothesized no-change value of 49 (p < 0.001). The mean scores for each of the 15 behaviors (excluding the two vaccination-related items) were significantly greater than the hypothesized no-change value of 3 (p < 0.001). The mean scores for the two vaccination-related items were significantly greater than the hypothesized no-change value of 2 (p < 0.001). Among all behaviors, avoiding dining out or gathering with friends had the highest mean score (Mean = 4.16), while engaging in regular physical activity had the lowest (Mean = 3.32). Avoiding dining out or gathering with friends had the highest percentage of individuals reporting an increase (71.3%), whereas maintaining a social distance of more than 1 m had the highest percentage of individuals reporting a decrease (17.5%). Regression analysis indicated that age, worry, positive coping, female sex, negative coping, and perceived severity were associated with the overall perceived change in protective behaviors, with worry being the most predictive variable.ConclusionThis study suggested that Chinese residents perceived an increase in their protective behaviors in the early stage after the policy change, with varying magnitudes across behaviors. We identified some potentially modifiable factors associated with perceived protective behavioral change, with worry emerging as the strongest predictor, followed by positive coping, negative coping, and perceived severity. These insights offer valuable information for developing effective communication strategies, psychological support, and comprehensive models in health behavior research.